Financing strategies for contract agricultural supply chain considering government subsidized interest - Jialuo Wang; Changhong Li; Yifan Shi (PLoS ONE, 2026)
This paper examines the financing strategy of capital-constrained farmers (traditional banking financing or e-commerce platform financing) and the government’s subsidy strategy (whether to subsidize) in the contract agricultural supply chain. The optimal decisions, profits, and social welfare are compared and analyzed under different scenarios, and the hybrid financing model is further extended. The study found that when the probability of normal production is low, it is optimal for the farmer to choose bank financing. The farmer’s choice of bank financing or platform financing is more profitable than the hybrid financing strategy in all cases. The platform can provide a short-term interest-free financing strategy to ensure the production and marketing of agricultural products. This study provides guidance on how to choose the financing strategy for the capital-constrained farmer and how the government implements subsidy policies.